Frequent emergency department visitors are frequent primary care visitors and report unmet primary care needs. Issue 3 (8th November 2016) - Cunningham, Amy; Mautner, Dawn; Ku, Bon; Scott, Kevin; LaNoue, Marianna
Abstract: A small percentage of emergency department (ED) visitors account for a disproportionate portion of ED visits. Little is known about their relationships with their primary care providers (PCPs). This study compares frequent and infrequent ED visitors' primary care utilization and perceptions of primary care access, continuity, and connectedness and examines primary care utilization and perceptions as predictors of ED use. Data were obtained from 2 cross‐sectional studies of psychosocial predictors of high levels of utilization at 2 urban hospitals. Data included age, sex, race/ethnicity, number and type of chronic conditions, self‐rated health, and number of primary care and ED visits in the previous 12 months. Participants also answered 8 primary care access, continuity, and connectedness items. Participants with frequent ED visits (N = 70) were younger (43.24 vs 48.34, P = .020), more likely to be African American (61.4% vs 41.8%, P < .001), had a significant chronic illness burden (5.83 vs 2.83 chronic conditions, P < .001), and were more likely to report fair or poor health (65.7% vs 50.4%, P = .009). Frequent ED users were as likely as infrequent users to have a usual source of care, and reported similar primary care access, relationship length, and likelihood of provider knowing them well. Although making twice as many primary care visits, these participants were less likely to report that they could get what they need from their PCP (76.12% vs 92.53%, P < .001). Despite similar primary care access and continuity, frequent ED visitors are less likely to report that they get what they need from their PCPs. Further research should investigate their needs and how primary care can best provide high‐value care to this complex population.